A Pragmatic Study of the Ratio Category: Statement of the Problem (Texas Journal of Philology, Culture and History, 2022)
This article analyzes the need to study the pragmatic aspect of the ratio category forms. Views on this have been critically studied. The author's concept of the study of ratio pragmatics is described.